4 Developing a framework to improve leadership performance in healthcare organisations: the case of the kingdom of saudi arabia. (31st October 2017) - Algarni, Namshan; Mclaughlin, Patrick; Al-Ashaab, Ahmed
Abstract : In order to improve leadership performance and enhance effective leadership in the healthcare sector organisations in general and the KSA in particular, this study proposes a theoretical framework to address the way in which leadership competency strengthens the relationship between leaders and followers. This research uses a constructive-interpretive philosophical approach, applying a qualitative strategy to achieve its objectives. The study aimed to identify the factors that related to performance level, including enablers and inhibitors of performance improvement. This helped to build an initial understanding about the context of the project and hence, address the critical factors and aspects that could be influencing leadership performance improvement in the healthcare sector in Saudi Arabia in order to develop a framework with suggested interventions to improve the productivity in this vital sector. Sampling of this study is the Health affairs of the Ministry of the Saudi National Guard. NGHA has also become well known internationally, especially in successful conjoined twins separations. Methodology: This study was exploratory and interpretive in nature. Hence, a grounded research methodology and an action research approach that was 'issue focused' were used to gain the perceptions of the participants from the organisational culture as an empirical data. Theoretical saturation was reached after 37 interviews. Research Findings: The findings suggested 71 factors that inhabit and enabler the leadership performance. All these factors grouped into 7 themes with the participants. These factors tend to employ behaviours and different aspects of cognitive, interpersonal qualities of leaders, fairness and equality, Islamic values and national culture. This result suggests that organisations in the healthcare sector can be benefited by giving more attention to these aspects in the future research. Themes located on the Schein's model of culture Self-assessment against the ideal position of themes In order to precisely evaluate the improvement in the culture of improving leadership performance in the healthcare sector, an assessment tool that centred on the performance culture archetype was developed from the harmonisation of the literature and the acquired data. Descriptive formations of leadership performance culture were developed for each of the themes. The objective of this assessment was to identify the themes that were farthest from the ideal position and use them as opening points for group discussions about mediations that might revolutionise the culture of improved performance. The participants evaluated their perceptions of the performance improvement culture by judging their proximity to each of the theme statements that signified an ideal position in the performance improvement culture. The suggested interventions should enable healthcare organisations to achieve the ideal positions of these developed themes.